(untitled) (International Journal of Engineering and Computer Science, 2014)
Security plays a vital role in all fields and in various applications. The existing computer security systems used at various places like banking, passport, credit cards, smart cards, PIN (Personal Identification Number), access control and network security are using username and passwords for person identification. In distributed system like ATM (Automated Teller Machine) the security is a main issue. The security level has been grown from providing PIN to Smart Card to Biometrics. Even though the security has been increased at the same time fraudulent activities have been grown to equal level. In the existing approaches different biometric technologies, multibiometrics, multimodal biometrics and two tier security is introduced in ATM to provide higher level of security. The proposed work is to enhance the security using brain fingerprinting technology which acts as an uncrackable password. A brain computer interaction has been developed to record the brain signal through Digital Electroencephalography. Brain fingerprinting is a technique used to find the unique brain-wave pattern generated by brain when a person encounters a familiar stimulus.